Tropospheric Refraction Modeling Using Ray-Tracing and Parabolic Equation - Valtr, Pavel; Pechac, Pavel (Radioengineering Society, 2005)
Refraction phenomena that occur in the lower atmosphere significantly influence the performance of wireless communication systems. This paper provides an overview of corresponding computational methods. Basic properties of the lower atmosphere are mentioned. Practical guidelines for radiowave propagation modeling in the lower atmosphere using ray-tracing and parabolic equation methods are given. In addition, a calculation of angle-of-arrival spectra is introduced for multipath propagation simulations.
Keywords: Radiowave propagation; Tropospheric refraction; Ray-tracing; Parabolic equation